Sensitivity and Specificity of Measuring Anti-Müllerian Hormone and Follicle Stimulating Hormone levels in Predicting Response to Ovarian Stimulation in Infertile Women - B Jabir Edan; H Mahdi Kadhim; H Resheed Behayaa (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul)
Background and Objective: Assisted reproductive technologies (ART), including in vitro fertilization (IVF) and embryo transfer, have achieved considerable success, largely due to controlled ovarian hyperstimulation (COH). However, there remains a shortage of studies on the estimation of various ovarian response markers linked to the GnRH agonist-controlled ovarian stimulation (COS) regimen. The objective of the current study is to assess the productiveness of Follicle Stimulating Hormone (FSH) and Anti-Mullerian Hormone (AMH) in determining ovarian responses in infertile patients undergoing controlled ovarian stimulation. Methods: This cohort study involved 90 females, aged 20 to 43 years, with primary and secondary infertility lasting between 3 and 13 years, attending the Al-Najef fertility center for ICSI cycles between June 2020 and January 2021. Patients with a history of ovarian surgery, polycystic ovary syndrome (PCOS), and premature ovarian failure (POF) were excluded. FSH and AMH levels were calculated on second 2 of the menstrual cycle, and the association between these indicators and outcome factors was evaluated. Findings: AMH demonstrated a negative link with age and a positive link with the antral follicle count, total number of follicles after induction, and retrieved oocyte count (p<0.05). FSH exhibited a significant negative link by the total number of follicles after induction (p<0.05). AMH demonstrated the best sensitivity and specificity, positive predictive value (PPV) and negative predictive value (NPV) for predicting ovarian response. Specificity, sensitivity, PPV and NPV for AMH with cut-off values >2 ng/mL test providing 84%, 80%, 86%, 57% in comparison to FSH with cut-off values >4 IU/mL yielded 67%, 68%, 50% and 54%, respectively. Conclusion: In conclusion, our findings suggest that AMH is a superior predictor of ovarian response compared to FSH.